PENGGUNAAN APLIKASI MEDIA MATH CITY MAP (MCM) UNTUK MENINGKATKATKAN KOMPETENSI PEDAGOGI GURU MATEMATIKA JENJANG SMP KECAMATAN DUKUHWARU KABUPATEN TEGAL - Anita Triyastuti; Kusrina, Tity (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this research is the low level of literacy and numeracy in the Education Report Cards of Junior High Schools (SMP) in Tegal Regency, where learning is still conventional and isolated within specific subjects. This study aims to evaluate the effectiveness of the Math City Map (MCM) application in improving the pedagogical competence of mathematics teachers in Dukuhwaru District. The research method used is a quantitative approach with a pre-experimental design (Pretest-Posttest).  The participants consisted of 10 teachers from 5 schools. Data analysis techniques included descriptive statistics, normality tests, homogeneity tests, and paired sample t-tests. The results showed a significant increase in the average score from 64.75 (pretest) to 85.35 (posttest), with a mean difference of 20.60 points. Statistical testing using the t-test yielded a p-value of 0.00003 (< 0.05), indicating a highly significant difference. Furthermore, regression analysis showed that the intervention contributed 69% to the final outcome. In conclusion, the application of MCM is effective in enhancing teachers' pedagogical competence and creating a contextual, meaningful learning atmosphere.